2019
DOI: 10.5902/1980509826869
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura e diversidade de trechos de Cerrado <i>sensu stricto</i> às margens de rodovias no estado de Minas Gerais

Abstract: Estradas são um dos principais fatores de degradação conhecidos do Cerrado, pois, apesar de sua relevância econômica, causam recortes em extensas massas contínuas de biota natural. De acordo com o Código Florestal Brasileiro, a vegetação às margens de rodovias deve ser considerada como de preservação permanente. Entretanto, escassos são os estudos que visam avaliar o real potencial conservacionista destas áreas. O objetivo do estudo foi avaliar o estágio de conservação do estrato arbóreo do Cerrado localizado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…Of the rare species sampled in the area, the E. dysenterica, B. crassifolia and L. pacari are typical of Cerrado, where they occur in densities greater than those found in the study area (COSTA et al, 2010;FERREIRA et al, 2010;. On the other hand, E. florida, L. molleoides and C. duarteanum are indicator species of seasonal deciduous forest with a greater number of individuals than reported for our study area (ARRUDA et al, 2011;SCHUMACHER et al, 2018).…”
Section: Speciesmentioning
confidence: 75%
See 3 more Smart Citations
“…Of the rare species sampled in the area, the E. dysenterica, B. crassifolia and L. pacari are typical of Cerrado, where they occur in densities greater than those found in the study area (COSTA et al, 2010;FERREIRA et al, 2010;. On the other hand, E. florida, L. molleoides and C. duarteanum are indicator species of seasonal deciduous forest with a greater number of individuals than reported for our study area (ARRUDA et al, 2011;SCHUMACHER et al, 2018).…”
Section: Speciesmentioning
confidence: 75%
“…As example, Ferreira et al ( 2017), considering a study area in Gurupi-Tocantins, found a diversity index of 3.52 to 3.70 nats.ind -1 , and Pielou equitability from 0.79 to 0.87. Also, Costa et al (2019) observed a diversity equal to 3.64 nats ind -1 , and Pielou equitability of 0.81 at the Triângulo Mineiro and Alto Paranaíba in Minas Gerais state. Our findings may be related to anthropic intervention, since our study fragment is located next to an urbanized area.…”
Section: Speciesmentioning
confidence: 85%
See 2 more Smart Citations
“…Populações que ocupam áreas mais próximas das rodovias estão sujeitas a processos de redução populacional e possível extinção local, em consequência da redução e fragmentação de áreas. Costa et al (2019) realizaram o levantamento do estágio de conservação florestal do cerrado localizadas ao longo das rodovias, concluindo que a paisagem no entorno de rodovias se tornou mais rala e esparsa, comprovado por baixos valores de densidade e área basal.…”
Section: Resultsunclassified